Blue Jeans - Rozier, Jacques; Jacquinet, Robert; Ferro, René; DePeretti, Francis; Klar, Élisabeth (Jacques Rozier, 2008)
The story of two seventeen year old boys. They are wearing medals around their necks. They have their pockets full of chewing gum something that they chew ceaselessly. They are wearing blue jeans. They spend the day along the beach front in Cannes looking for girls to win over. [letterboxd.com]